Modeling the demand for electricity for the family sector in ‎Algeria according to the H.R LINDEN model - Dilmi, Lakhdar; Delhoum, Khalida (Dirassat Journal Economic Issue, 2016)
Energy demand is considered to be one of the important issues currently under discussion in all states, due to its characteristics including electricity. The latter is a vital material and important economic product whose demand increases from day to day. Of great intensity and accelerated pace. This has prompted the majority of countries to seek in-depth and intense solutions capable of meeting the electricity consumption needs of its growing individuals. This is why this subject forms the core of our present study which is mainly interested in showing the image of the modeling of electricity demand in the household sector, and as a case study, we have chosen Algeria by adopting the HR LINDEN model (1950-1970) from annual data in the period 1970-2009 to better understand to what extent this model can give us precise results and which is close to reality, and which can be data supports to plan and make future decisions